(untitled) (Patan Gyansagar, 2025)
Historically, Hattisar was integral to royal hunting and later integrated into national park conservation. This paper aims to analyze the job description, facilities, and challenges of the staff of Hattisar. The study used descriptive and exploratory research designs to examine staff roles, services, and challenges at Hattisar in Bardiya National Park. Data were gathered from official records, interviews, and focus group discussions, and analyzed using both qualitative and quantitative methods to provide a comprehensive overview. The staff are primarily Tharu indigenous people and perform crucial tasks such as elephant care, anti-poaching patrols, and tourism support. Despite their contributions being very important, the study shows that they face major problems in contract-based employment. inadequate infrastructure and resources, high occupational risks due to wildlife encounters or natural hazards.